Clonal diversity of Clostridium perfringens human clinical isolates with various toxin gene profiles based on multilocus sequence typing and alpha-toxin (PLC) typing. (December 2021) - Aung, Meiji Soe; Matsuda, Asami; Urushibara, Noriko; Kawaguchiya, Mitsuyo; Ohashi, Nobuhide; Matsuda, Norifumi; Nakamura, Mayumi; Ito, Masahiko; Habadera, Satoshi; Matsumoto, Akinori; Hirose, Mina; Kobayashi, Nobumichi
Abstract: Objectives: Clostridium perfringens is a common anaerobic pathogen causing enteritis/enterocolitis and wound infections in humans. We analyzed clonal diversity and toxin gene prevalence in C. perfringens clinical isolates from humans in northern Japan. Methods: Prevalence of nine toxin genes was analyzed for 585 C. perfringens isolates from patients collected for 20-month period between May 2019 and December 2020 by molecular methods. Sequence type (ST) based on multilocus sequence typing (Xiao's scheme) and alpha-toxin (PLC) sequence type were determined for a total of 124 isolates selected in the present study along with those in our previous study (2017–2018). Results: Toxinotypes A (68.2%) was the most frequent, followed by F (31.6%), and G (0.2%), while additional toxin genes encoding binary enterotoxin (BEC/CPILE) and beta2 toxin were identified in one and six isolates, respectively. Among the 124 isolates with various toxin gene profiles, 62 STs including 53 novel types were identified, revealing the presence of six clonal complexes (CCs) consisting of 27 STs. Most of enterotoxin gene ( cpe )-positive isolates belonged to CC36, CC41, and CC117. Based on 22 key amino acids in alpha toxin sequence, four PLC types (I-IV) including 21 subtypes were classified, and their relation to individual STs/CCs was clarified. Two isolates harboring bec/cpile belonged to different STs (ST95, ST131) and PLC types (If, IVb), indicating distribution of this toxin gene to distinct lineages. Conclusions: The present study revealed the diversity in C. perfringens clones of human origin with various toxin gene profiles represented by ST/CC and PLC type. Highlights: ST and toxin genes were analyzed for 124 Clostridium perfringens clinical isolates. 62 STs including 53 novel STs were identified, revealing six clonal complexes. CC36, CC41, and CC117 contained most of enterotoxin gene ( cpe )-positive isolates. Alpha-toxin (PLC) was classified into four types (I-IV) including 21 subtypes. Two bec/cpile -positive isolates belonged to different STs with distinct PLC types.